Guidelines for Administration of Service Units of Regional Special Education Center 8, Chiang Mai Province - Khaesor, Arthit; Buacharoen, Parichat (Journal of Graduate MCU KhonKaen Campus, 2023)
The purpose of research objectives is 1) to study the current and desirable conditions of Service unit administration of Regional Special Education Center 8, Chiang Mai. 2) to study administrative guideline service unit of Regional Special Education Center 8, Chiang Mai. and 3) to assess the suitability and feasibility of service unit administration for the Regional Special Education Center 8, Chiang Mai. The population used in this research were administrators, heads of the four administrative groups, teachers and staffs who work either in the service unit or Regional Special Education Center 8, Chiang Mai, totaling 97 people. The tools used were questionnaires and interview forms. Data analysis using basic statistics, including mean, standard deviation. and content analysis The results of the research revealed that 1) The current state of administration of the service unit for the Regional Special Education Center 8, Chiang Mai, the current condition is at a high level. As for the desirable conditions for the administration of the service unit of the Regional Special Education Center 8, Chiang Mai had the desirable condition at the highest level. The curriculum has been developed according to the guidelines of the Regional Special Education Center 8, Chiang Mai is consistent with the context of the service unit there is a service plan. Personnel Management Personnel positions are allocated to a variety of professions. and sufficient for the number of students in the service unit employees are encouraged to realize their roles and responsibilities. General Administration, Mobilize resources to support the improvement of the environment and school buildings. Budget management, The service unit is involved in the planning. Teaching and learning management equipment is supported. Student lunch budget is allocated, and others related to teaching and learning and prepare an operational action plan supervision Summary of monitoring results to be used for improvement and development. It was found that they were appropriate at the highest level. and a feasibility assessment of the service unit administration of the Regional Special Education Center 8, Chiang Mai. It was found that there was a high level of possibility.